Nachhaltige Entwicklung der Landwirtschaft: Förderung von Biodiversität und Klimaneutralität - Silke Hüttel; Oliver Mußhoff (Wirtschaftsdienst, 2024)
– To promote biodiversity, a diverse landscape is necessary. Structural change in agriculture and increasing cost pressure have led to the trend of fewer farms and larger farming units with less diversity. Reversing this trend is a societal task that requires a willingness to make sacrifices. For agriculture, we suggest combining new technologies and artificial intelligence to foster 'new' ways of thinking for place-based solutions. That is, land management oriented towards natural habitats and more diversity, which is equally economically viable. It is essential to visibly reward the ecological added value.
Keywords: Q10; Q18; Q24; Q57; R14; 330; Landwirtschaft; Ökologischer Landbau; Nachhaltige Entwicklung; Deutschland; Landwirtschaft; Ökologischer Landbau; Nachhaltige Entwicklung; Deutschland